Phenolic Compounds from the Aerial Parts of Adenophora triphylla (Thunb.) A. DC. var. triphylla and their Free Radical Scavenging Activity - Hori, Kengo; Devkota, Hari Prasad (Nepal Journal of Biotechnology, 2020)
Adenophora triphylla (Thunb.) A. DC. var. triphylla (Family: Campanulaceae) is distributed in Japan, Korea, and China. It is locally known as “Saiyousyajin” in Japan and the roots are used in traditional medicine to treat chronic bronchitis and whooping cough, and also as anti-inflammatory and anti-tussive agents. Till now, there is no report on the chemical constituents of aerial parts. Thus, the main aim of this study was to isolate and identify major chemical constituents of aerial parts of A. triphylla var. triphylla, and to evaluate their free radical scavenging activity. The 70% methanol extract of the aerial parts was subjected to repeated column chromatography using MCI gel CHP-20P, Sephadex LH-20, ODS and silica gel columns to isolate the five phenolic components (1-5). Free radical scavenging activity of the extract and compounds was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity method. The structures of the isolated compounds were elucidated as luteolin (1), luteolin 4’-O-b-glucopyranoside (2), luteolin 7-O-b-glucopyranoside (3), luteolin 7-O-neohesperidoside (4) and chlorogenic acid (5) based on their nuclear magnetic resonance (NMR) spectral data and comparison with literature values. All these compounds were isolated for the first time from A. triphylla var. triphylla. Extract showed weak free radical scavenging activity. Among isolated compounds, luteolin (1), luteolin 7-O-b-glucopyranoside (3), luteolin 7-O-neohesperidoside (4) and chlorogenic acid (5) showed potent free radical scavenging activity. Results from this study suggest that the aerial parts of A. triphylla var. triphylla might be a potential plant source for the development of functional foods, however further detailed research is necessary.